THE EFFECT OF MONETARY POLICY ON CAPITAL MARKETS IN DEVELOPING COUNTRIES - Loso Judijanto; Fauziah Nur Hutauruk; Amândio de Araújo Sarmento; Al-Amin (Adisam Publisher, 2025)
Monetary policy is recognised as having a significant influence on the economy, particularly through its impact on the capital market. The study conducted in this research uses the literature research method. The results found that the eflects of interest rate changes and significant increases in liquidity often have a short-term positive impact on stock market indices. However, the findings also emphasise the need for policymakers to consider complicating factors such as global political or economic instability and high inflation expectations, which may reduce the eflectiveness of monetary policy. Finally, the findings underline that the room for manoeuvre of monetary policy can be limited in a low interest rate environment, which calls for a more innovative and sensitive policy approach to external conditions.